A Wideband Fat Dipole Antenna Integrated with Solar Cells for Internet of Things Applications - Wang, Heesu; Ali, Ahmed; Park, Ikmo (2023 IEEE International Symposium on Antennas and Propagation, ISAP 2023, 2023)
This paper presents a solar cell–integrated wideband fat dipole antenna. Implementing a dipole antenna with a solar cell provides dual functionality that simultaneously enables energy harvesting and wireless communication. RF decoupler circuits are used to operate the antenna and the solar cell independently. The proposed design uses a fat dipole structure incorporating a wide dipole arm and a pair of open stubs. These features make the antenna have wideband characteristics and a high-form factor. The proposed solar cell integrated antenna has overall dimensions of 102 mm × 52 mm × 0.571 mm (0.333 λo × 0.170 λo × 0.0019 λo at 0.98 GHz). It exhibits a –10 dB impedance bandwidth of 105% (ranging from 0.98 to 3.18 GHz), a form factor of 96%, and an optical transparency of 100%.
Keywords: Decouplers; Design use; Fat dipole antennas; Form factors; Integrated antennas; Integrated wideband; Solar cell antenna; Wide-band; Wideband antenna; Wireless communications; dipole antenna; integrated antenna; solar cell antenna; wideband antenna